CHINESE CHARACTER CHALLENGER 汉 字 挑 战 者 Supplementary courseware for assisting students learning Chinese characters - Yu, Xiao Ping (Amy) (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Modern Foreign Languages))--University of Stellenbosch, 2005.